Window on freedom : race, civil rights, and foreign affairs, 1945-1988 - Plummer, Brenda Gayle (Chapel Hill ; London : The University of North Carolina Press, 2003)
Demonstrates how US foreign policy has been embedded in social, economic and cultural factors of domestic and foreign origin. It argues that the campaign to realize full civil rights for racial and ethnic minorities in the US is best understood in the context of competitive international relations.
Seen from the outside : the international perspective on America's dilemma / Paul Gordon Lauren -- Race from power : U.S. foreign policy and the general crisis of white supremacy / Gerald Horne -- Brown babies : race, gender, and policy after World War II / Brenda Gayle Plummer -- Bleached souls and Red Negroes : the NAACP and Black Communists in the early Cold War, 1948-1952 / Cary Fraser -- An American dilemma : race and realpolitik in the American response to the Bandung Conference, 1955 / Cary Fraser -- Segregationists and the world : the foreign policy of the white resistance / Thomas Noer -- The unwelcome mat : African diplomats in Washington, D.C., during the Kennedy years / Michael Krenn -- Birmingham, Addis Ababa, and the image of America : international influence on U.S. civil rights politics in the Kennedy administration / Mary L. Dudziak -- Antiwar Aztlán : the Chicano movement opposes U.S. intervention in Vietnam / Lorena Oropeza -- From Cold War to global interdependence : the political economy of African American antiapartheid activism, 1968-1988 / Donald R. Culverson.
Includes bibliographical references (pages 239-249) and index.
Online resource (HeinOnline, viewed August 3, 2021).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: United States -- Foreign relations -- 1945-1989.; United States -- Race relations -- Political aspects; Racism -- Political aspects -- United States -- History -- 20th century; African Americans -- Civil rights -- History -- 20th century; Minorities -- Civil rights -- United States -- History -- 20th century; United States -- Foreign relations -- Developing countries; Developing countries -- Foreign relations -- United States; Electronic books; Racisme -- Aspect politique -- États-Unis -- Histoire -- 20e siècle.; Noirs américains -- Droits -- Histoire -- 20e siècle.; Minorités -- Droits -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Relations extérieures -- 1945-1989.; États-Unis -- Relations raciales -- Aspect politique; États-Unis -- Relations extérieures -- Pays en voie de développement.; Pays en voie de développement -- Relations extérieures -- États-Unis.; Livres numériques.; e-books.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; African Americans -- Civil rights; Diplomatic relations; Minorities -- Civil rights; Race relations -- Political aspects; Racism -- Political aspects; Developing countries; United States; Außenpolitik; Bürgerrecht; Ethnische Beziehungen; USA; Rassenverhoudingen; Burgerrechten; Buitenlandse betrekkingen; Racisme -- Aspect politique -- États-Unis -- 1945-1990.; Noirs américains -- Droits -- 1945-1990.; Minorités -- Droits -- États-Unis -- 1945- ...; États-Unis -- Relations interethniques -- Aspect politique -- 1945-1990.; États-Unis -- Relations extérieures -- 1945-1989.; Etats-Unis -- Relations interethniques -- 1945-1990.; Etats-Unis -- Relations extérieures -- Pays en voie de développement -- 1945-1990.; Pays en voie de développement -- Relations extérieures -- Etats-Unis -- 1945-1990.; 1900-1999; History